HPLC-QTOF-MS-based chemical profiling of Pulicaria undulata and its influence on high-sucrose diet-induced diabetic-linked biochemical attributes and oxidative stress associated ovarian damage in Drosophila melanogaster - Mohammed Alsafran (11482987) (2025)
In the State of Qatar, Pulicaria undulata (L.) C.A.Mey (family: Asteraceae) has been traditionally used to treat various diseases, including diabetes. However, the chemical components responsible for its antidiabetic activity and its role in managing diabetes-linked complications remain unidentified. Hence, in the present study, we explored the chemical composition of the ethanol extract of P. undulata using high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (HPLC-QTOF-MS) and investigated its effects on high sucrose diet (HSD)-induced diabetic-linked biochemical attributes and oxidative stress-associated ovarian damage in Drosophila melanogaster. For HPLC-QTOF-MS profiling, the mass spectra were acquired in auto MS/MS mode, and the identification of compounds was performed by analyzing the exact mass fragments and considering the mass error. Later on, the flies were treated with 0.062, 0.25, and 0.5 mg/mL of the extract containing the HSD diet for ten days, and biochemical perturbations were investigated. Around 31 different compounds were identified in the ethanol extract of P. undulata, including 17 triterpenoids, 4 fatty amides, 3 flavonoids, 2 polyphenols, 2 carbohydrates, 2 amino acids, and one alkaloid. Among treatments studied, only the 0.125 mg/mL treatment alleviated HSD-induced diabetic-linked biochemical attributes, such as glucose, cholesterol, and triglycerides, including oxidative stress markers such as reactive oxygen species (ROS) and catalase activity. All treatments above and below this effective dose showed negative effects. Conclusions Both antioxidant and prooxidant compounds were found in P. undulata, and their synergistic and antagonistic effects may define the beneficial and toxic outcomes of this valuable herbal medicine. Other Information Published in: Bioorganic Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.bioorg.2025.108890